Texas by Terán : the diary kept by General Manuel de Mier y Terán on his 1828 inspection of Texas - Mier y Teran, Manuel de (Jack and Doris Smothers series in Texas history, life, and culture ;, 2000)
Acknowledgments -- Introduction -- The diary: "Texas by Terán, his journey, 1828"--Diary: Béxar to Nacogdoches -- Terán's letters from Nacogdoches -- Diary: trip to the Red River -- Diary: trip down the Trinity -- Diary: Nacogdoches to Matamoros -- Diary: up the Rio Grande to Mier -- Epilogue -- Appendix: Pavie's view of East Texas -- Notes -- Bibliography -- Index.